Measurement of the effects of capital structure in enterprises on the probability of bankruptcy: A research on the enterprises traded in the BIST industrial index - ÖZER, Gökhan; ÖZEN, Ali Korhan (Journal of Economics Library, 2018)
Abstract. This study aims to measure the relationship between the Altman Z-Score, which is used to determine the financial failure of the enterprises, and the decisions on the capital structure. In other words, it has been tried to determine whether the capital structure has any effect on the risk of bankruptcy. In the scope of the research, 112 enterprises that continue their activities uninterruptedly and are traded on the industrial index between 2006 and 2014 have been examined. Panel data analysis has been utilized in order to examine the effect of capital structure on the financial failure and/or performance in the enterprises. Through the use of the Altman Z-Score (ZSCORE) which is an indicator of the risk of bankruptcy in the models formed based on the panel data analysis, a statistically negative and significant correlation has been found between the capital structure of the enterprises and the risk of bankruptcy. The leverage ratio (TBTV), which is considered as a variable that represents the capital structure, and thenon-debt tax shields (BDVK), which represent the control variable, have been used. In the correlation between the control variable and the ZSCORE, it has been found that the BDVK has not any significant effect on the ZSCORE and has not caused any increase in the total variance. The findings of this study indicate that the debt ratio in the enterprises causes an increase in financial failure, and they are also compatible with the validity of the trade-off theory. Keywords. Capital structure, Altman Z Score, Panel Data, Financial Performance, Trade-Off Theory, BIST. JEL. C23, G32, G33.